The influence of absorptive capacity on product innovation in Southern Brazilian industries. (2018) - Engelman, Raquel; Schmidt, Serje; Froehlich, Cristiane; Fracasso, Edi Madalena
The aim of this paper is to investigate the influence of absorptive capacity (ACAP) on product innovation in industries of Rio Grande do Sul, the southernmost state of Brazil. A total of 391 southern Brazilian firms of different sizes, from different sectors and technological intensities were considered by using a quantitative approach and structural equation modelling. The main results on this research confirm the influence of ACAP on innovation. More than 30% of innovations can be attributed to absorptive capacity. Furthermore, different dimensions of ACAP impact innovations in different ways, depending on the firm's technological intensity. The paper contributes to a better understanding of these topics. The results showed which dimensions have a different influence on product innovation, considering firm's technological intensity, which is an important finding to managerial practice. In terms of theoretical implications, the study's results show that ACAP has three dimensions, as initially proposed, rather than two or four.